Éléments Introductifs et Cadres Conceptuels de la Sécurité Alimentaire : Prospectives de l’Approche “Agrifood Systems" - Frija, Aymen; Sghaier, Mongi; Darghouth, Mohamed Aziz (International Center for Agricultural Research in the Dry Areas, 2024)
This presentation offers an introduction to the concepts of agrifood systems for a broad and multidisciplinary audience, contrasting with the classical approach of food security dimensions. It also relates the concepts of agrifood systems and agroecology and prepares for a subsequent presentation on the application of strategic foresight scenarios development for food security and agroecology transition.